Research Ethics in Obstetrics and Gynecology - Suthee Panichkul (The Royal Thai College of Obstetricians and Gynaecologists, 2018)
Women should be presumed eligible to participate in obstetrics and gynecology studies. The potential for pregnancy should not automatically exclude a woman from participating in a study although the use of contraception may be required to participate. A significant concern in moving forward with enrolling pregnant women in research is that an intervention could cause harm to the fetus, and especially that the intervention or medication under study could cause a birth defect or other harms. Researchers and research ethics committees must ensure that potential research participants are adequately informed about the risks to breastfeeding women and their infants, and about the risks to pregnant women (including future fertility), their pregnancies and their fetuses. When evidence concerning risks is unknown or conflicting, this must be disclosed to the pregnant or breastfeeding woman as part of the informed consent process.